Cyclical investment behavior across financial institutions - Yannick Timmer (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2018)
This paper contrasts the investment behavior of different financial institutions in debt securities as a response to past returns. For identification, I use unique security-level data from the German Micro-database Securities Holdings Statistics. Banks and investment funds respond in a pro-cyclical manner to past security-specific holding period returns. In contrast, insurance companies and pension funds act counter-cyclically; they buy when returns have been negative and sell after high returns. The heterogeneous responses can be explained by differences in their balance sheet structure. I exploit within-sector variation in the financial constraint to show that tighter constraints are associated with relatively more pro-cyclical investment behavior.
Keywords: G11; G15; G12; G21; G22; G23; 330; Portfolio Allocation; Investment Behavior; Financial Markets; Debt Securities; Balance Sheet Constraints